Attitudes of Foreign Tourists Towards Tourism in Luang Prabang Province - Heuangphoxay, Vilaythong (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aimed to: 1) examine foreign tourists' perceptions of tourism in Luang Prabang, 2) assess their attitudes toward tourism in the province, and 3) analyze the relationship between their perceptions and attitudes. The research followed a quantitative approach. The sample consisted of 384 foreign tourists visiting Luang Prabang Province, selected using non-probability convenience sampling. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) to determine frequency, percentage, mean, standard deviation, and Pearson correlation coefficient. The findings revealed that Perceptions: Overall, foreign tourists’ perceptions of tourism in Luang Prabang were at a high level. The dimensions of psychological factors, tourist attractions, value, and potential were perceived at the highest level, while communication was also rated highly. Attitudes: Foreign tourists’ overall attitudes toward tourism in Luang Prabang Province were also high. High ratings were given for services, attractiveness, facilities, and accessibility of attractions. The highest ratings were for activities and accommodation at attractions. Relationship between Perception and Attitude: There was a strong positive correlation between foreign tourists’ perceptions and their attitudes toward tourism in Luang Prabang Province, with statistical significance at the 0.01 level.